2016
DOI: 10.1002/micr.30100
|View full text |Cite
|
Sign up to set email alerts
|

The free medial sural artery perforator flap: Versatile option for soft tissue reconstruction in small‐to‐moderate size defects of the foot and ankle

Abstract: The MSAP flap provides thin soft tissue coverage, enabling good functional recovery after defect reconstruction all around the foot and ankle, with evident advantages in the midfoot. However, the functional outcomes after reconstruction of the ankle-hindfoot or hallux region depend on the preexistent functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Scores were reported to be statistically insignificant for the subjective qualityof-life measurement using the SF-36. This study concluded the free MSAP flap a reliable option in reconstruction of small-to-moderate sized defects of the foot and ankle due to its thin and pliable aesthetic appearance and its evident advantages in the midfoot (p = 0.265) with a reliable vascular pedicle [8].…”
Section: Free Medial Sural Artery Flapmentioning
confidence: 72%
See 3 more Smart Citations
“…Scores were reported to be statistically insignificant for the subjective qualityof-life measurement using the SF-36. This study concluded the free MSAP flap a reliable option in reconstruction of small-to-moderate sized defects of the foot and ankle due to its thin and pliable aesthetic appearance and its evident advantages in the midfoot (p = 0.265) with a reliable vascular pedicle [8].…”
Section: Free Medial Sural Artery Flapmentioning
confidence: 72%
“…Free tissue transfer has been considered the mainstay of treatment for reconstruction of the traumatized lower limb over the past few decades due to local and regional flaps often having an unreliable blood supply and insufficient local donor tissue [18]. The most widely used and most suited free flap for reconstruction of soft tissue defects of the lower extremity is said to be the free ALT flap [8,9]. When undergoing reconstruction for diabetic foot ulcers the goal in treatment by way of free tissue transfer is to provide a flap with adequate bulk, shock absorption, and durability against the shearing forces of ambulation [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 In addition, all patients were evaluated with the American Orthopaedic Foot and Ankle Society (AOFAS) clinical rating system, which is the most commonly used outcome tool to assess the results of treatment of foot and ankle disorders. 21 The clinician-based questionnaire has four versions, each specific according to the function of the anatomic region of the foot and ankle. Here, we only assessed the AOFAS ankle-hindfoot score.…”
Section: Outcome Measuresmentioning
confidence: 99%